The Effect of Environmental-Based Guided Inquiry Learning Model on the Competence of Science Students in Tarusan - Rintia Mawaddah; Helendra Helendra; Ganda Hijrah Selaras; Ardi Ardi (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The lack cognitive competency os caused by a problem when learning begins, in the learning model used does not involve active students in learning. How to overcome thatis done to increase the students' cognitive competency is to apply an guided inquiry learning model based environment at SMPN 2 Koto XI Tarusan in KD. 3.7 material interaction of living things with their environment. This research used a Randomized Control Group Posttest Only Design. The population in this study were all student VII SMPN 2 Koto XI Tarusan. Sampel was taken by purposive sampling technique. The hypothesis testing using the t test. The results of data analysis in the research obtained in a cognitive competency that tcount>ttable (1.70>1.67). So, the conclusion of the guided inquiry learning model baased environment give a meaningfull effect on student' cognitive competency